Reaching for the sun : how plants work - King, John, 1938- 4 0 16; 5 (Cambridge, UK : Cambridge University Press, 2011)
Examines the ways in which plants grow and develop by exploring such aspects as photosynthesis, reproduction, and dormancy. Also analyzes their growth patterns, their survival tactics, and what gives them color, fragrance, and flavor.
Includes bibliographical references and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Plants.;Botany. -- 20; 20; 2